Pelatihan Lilin Aromaterapi Berbasis Minyak Jelantah Untuk Pemberdayaan dan Ekonomi Sirkular - Susanti Susanti; Tias Ernawati; Kusmendar Kusmendar; Tri Yulianto; Rahmawati Endah Witanti; Anisa Dwi Maslikhah (Indonesian Journal Publisher, 2025)
The community in Pedukuhan Bakung, Yogyakarta, faces challenges in managing used cooking oil waste, which is often improperly disposed of, leading to environmental pollution. This community service program aimed to address this issue by empowering local youth through training on converting used cooking oil into valuable products. The training was attended by 10 youths from Pedukuhan Bakung, who gained an understanding of the environmental impacts of used cooking oil and practical skills in producing aromatherapy candles from purified used cooking oil. The program included socialization on the environmental impacts of used cooking oil, demonstrations of the purification process, and hands-on practice in making aromatherapy candles. Based on questionnaire evaluations, the program achieved an average success rate of 89.5%, with material clarity and direct benefits rated at 92.5%. Participants gave the highest rating of 95% for gaining new insights, reflecting the program's success in enhancing understanding of the circular economy. However, participants’ motivation to utilize used cooking oil as a valuable product still requires improvement, with a score of 85%. The training results demonstrated a significant increase in participants' environmental awareness and skills, as well as new economic opportunities through the utilization of used cooking oil. Several participants expressed interest in independently producing aromatherapy candles as an additional business opportunity. Follow-up training focusing on product diversification and marketing strategies is recommended to maximize the economic impact. This program successfully integrated environmental and economic aspects within the circular economy concept, providing the potential for sustainable benefits for the community.